Childhood abuse and depression in adulthood: The mediating role of allostatic load. (August 2018) - Scheuer, Sandra; Wiggert, Nicole; Brückl, Tanja Maria; Awaloff, Yvonne; Uhr, Manfred; Lucae, Susanne; Kloiber, Stefan; Holsboer, Florian; Ising, Marcus; Wilhelm, Frank H.
Highlights: Allostatic load represents a multi-system measure of physiological dysregulation. Allostatic load mediated the influence of childhood trauma on depression in adulthood. Frequency of childhood physical abuse was associated with allostatic load in adults. Allostatic load in adulthood in turn was related to depression risk. Future research should identify allostatic load biomarkers prospectively. Abstract: Background: Traumatic experiences during childhood are considered a major risk factor for depression in adulthood. Childhood trauma may induce physiological dysregulation with long-term effects of increased allostatic load until adulthood, which may lead to depression. Thus, our aim was to investigate whether allostatic load – which represents a multi-system measure of physiological dysregulation – mediates the association between childhood trauma and adult depression. Methods: The study sample consisted of 324 depressed inpatients participating in the Munich Antidepressant Response Signature (MARS) project and 261 mentally healthy control participants. The mediation analysis using a case-control approach included childhood trauma, i.e., physical and sexual abuse, as predictor variables and an allostatic load index comprised of 12 stress-related biomarkers as mediator. Age and sex were included as covariates. Results: Mediation analyses revealed that the influence of physical abuse, but not sexual abuse, during childhood on depression in adulthood was mediated by allostatic load. This effect was moderated by age: particularly young (18–42 years) and middle-aged (43–54 years) adults with a history of physical abuse during childhood exhibited high allostatic load, which in turn was associated with increased rates of depression, but this was not the case for older participants (55–81 years). Conclusions: Results support the theoretical assumption of allostatic load mediating the effect of physical abuse during childhood on depression in adulthood. This predominantly holds for younger participants, while depression in older participants was independent of physical abuse and allostatic load. The effect of sexual abuse on depression, however, was not mediated by allostatic load. Identifying allostatic load biomarkers prospectively in the developmental course of depression is an important target for future research.